PENGARUH AIR KELAPA (Cocos Nucifera) TERHADAP PERTUMBUHAN TANAMAN HIAS - Irmayanti, Amanda; Dewi, Lussana Rossita (Institute of Computer Science (IOCS), 2025)
Ornamental plants have aesthetic roles and environmental benefits, but their care often requires chemicals that are less environmentally friendly. This study aims to evaluate the potential of young coconut water (Cocos nucifera) as a natural plant growth regulator (PGR) through a literature study. Coconut water is rich in nutrients, growth hormones (auxins, cytokinins, gibberellins), and other bioactive compounds, which can support various aspects of ornamental plant growth. The literature study included 15 relevant studies from 2016–2024, which evaluated the effect of coconut water concentration on various parameters, such as number of leaves, root length, and number of shoots in various ornamental plant species. The results showed that coconut water provided significant benefits, especially at concentrations of 15–20%, although plant responses varied depending on species and environmental conditions. In the in vitro culture method, coconut water was shown to replace synthetic hormones such as cytokinins with high effectiveness. The combination of coconut water with other ingredients, such as peptone and gibberellins, also increased plant growth, although some studies noted insignificant effects under certain conditions. These findings confirm that coconut water can be an economical and sustainable natural PGR alternative to enhance the growth of ornamental plants. However, further research is needed to optimize its use in various types of plants and environments.